The effects of rapid and prolonged changes in blood pressure on cerebral blood flow in healthy humans : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy, Massey University, Manawatu, New Zealand - Perry, Blake G (Massey University, 2014)
The regulation of blood flow to the brain is complex and incompletely understood. Many local and systemic factors modulate cerebral perfusion, one of which is arterial blood pressure. The brain possesses intrinsic mechanisms which act to protect against rapid and also prolonged changes in perfusion pressure. However, recent evidence indicates that this supposedly powerful regulatory mechanism/s may not be as efficient as traditionally believed and that changes in arterial blood pressure have a profound effect on cerebral blood flow (CBF). This thesis explored different non-pharmacological means of perturbing mean arterial blood pressure (MAP) both rapidly (dynamic) and for prolonged steady-state periods (~5 min; static). Dynamic changes in blood pressure were induced via upright resistance exercise (Chapter Five) and standing Valsalva manoeuvres (VM; Chapter Six), while static changes were induced via lower body positive pressure (Chapters Seven and Eight). The effects of these changes in MAP on cerebral blood flow were assessed via transcranial Doppler ultrasound of the blood velocity in middle cerebral artery (MCAv). The findings of Chapter Five illustrated that during resistance exercise the peak mean MCAv (MCAvmean) was unchanged between loads despite the increasing MAP with the increasing relative load. Following resistance exercise, however, the hypotension observed was matched by concomitant reductions in MCAvmean, the magnitude of which was load dependent. Chapter Six investigated the role of the Valsalva manoeuvre (VM) alone in the stability of the MCAv response whilst standing. Chapter Six highlights that the VM protects the cerebral vessels during acute hypertension. In addition, more intense straining during a VM produced a similar response following the release of the manoeuvre to that seen following the resistance exercise. Thus, more pronounced decreases in blood pressure, whilst upright, do result in concomitant decreases in MCAvmean. The steady-state elevations in MAP examined in Chapters Seven and Eight increased MCAvmean with and without hypercapnia. Thus, illustrating that even when the regulatory mechanisms were functionally intact (normocapnia) the brain demonstrated a pressure passive relationship during relatively small increases in MAP. Overall, both abrupt and steady-state changes in perfusion pressure were coupled with alterations in MCAvmean. This thesis contributes to the notion that the cerebral circulation is not independent of changes in MAP, and that sustained hypercapnia impairs the autoregulatory capacity of the cerebral circulation. Importantly, this thesis shows these effects without the use of pharmacological agents to confound the interpretation of the data.
Keywords: Cerebral circulation; Blood pressure